Narrativas de professoras e elaboração de atividades impressas: diferentes percursos, saberes diversos - Tânia Maria da Silva (2020)
This research was developed at PROMESTRE, FAE / UFMG, following the Didactics and teaching line, woks with the teaching and learning processes, focused in Didactics. One side of the problem: what we can understand about the relationship between the teaching knowledge and the teaching process, more specific, in its operational dimension: the development of printed activities. In tune with the studies that dialogue with the concept of epistemology of teaching practice (FRANCO, 2014; ROLDÃO, 2007; TARDIF, 2014); it aims to reflect upon teacher’s knowledge and the development of printed activities starting with narratives of teachers from 4th and 5th grades of Elementary School - Initial Years of a public school in Belo Horizonte. The methodological approach used is autobiographical research due to the articulation between the specificities of this field of investigation and the research purpose. Starting from the theory that the subjects are constituted through biography processes, it allows access to subjective constructions crossed by the historical and social world and formative process through experiences of self-reflection. (DELORY-MOMBERGER, 2016; BOLÍVAR, 2012; SOUZA, 2006). The participants are three teachers from the 4th and the 5th grade from the same public school in Belo Horizonte. The sources of information consisted of narratives from oral and written interviews; printed activities developed by the participants and analysis sheets for those activities. The circular analysis process was composed of three stages: first signs, identification of the analysis units and interpretative analysis (SOUZA, 2006). The results show that the teaching knowledge is constructed and reconstructed along the personal and professional path, in a temporary, singular and compound way, remodeling as part of others. The research provides reflections about experiences before teaching, evolution education, pedagogical tradition, professional socialization and the teaching experience itself. The analyzes reveal an articulation between know-how and the choices in the development of printed activities; the teaching actions and decisions are based on these. It points out the formative power of professional socialization and the importance of reframing collective formative processes in a perspective focused on reflexive action. Point out that activities’ problems (typology and intentionality) from, mainly, internet help to reshape knowledge. As for educational resource, a book called “Different paths, several knowledges” was produced, which involves written and audiovisual record (comic strip and cartoons), it has as aim the self-reflection of the teacher/reader.